A coupled thermo-hydro-geochemical model for standing column well subject to CO2 degassing and installed in fractured calcareous aquifers. (September 2017) - Eppner, F.; Pasquier, P.; Baudron, P.
Abstract: Standing column wells, used to provide heating and cooling to buildings, allow significant energy savings. Nonetheless, variations of groundwater geochemistry, caused by temperature changes and CO 2 degassing, may favor minerals scaling in the well, associated equipment and the aquifer, which may lead to operational problems. This paper presents a coupled thermo-hydro-geochemical model that allows for predicting reaction rate of calcite. Once applied to a case study representative of a typical configuration, simulations indicate that precipitation, strongly dependent on temperature, mainly occurs at the inlet of the well in summer. Moreover, when the well is not perfectly sealed, degassing may enhance precipitation rate up to 33%. Finally, fracture clogging is avoided when a constant bleed of 10% is applied. This study evidences that the greatest risk of precipitation occurs when the standing column well is subject to degassing, operated with a bleed and installed in a fractured aquifer. Highlights: Development of a thermo-hydro-geochemical model applied to standing column wells. Mixed kinetic and equilibrium formulation used for coupling transport of dissolved chemical species with kinetic and equilibrium reactions. The reaction rate of calcite is strongly dependent on temperature and CO 2 degassing. Limiting degassing may enhance the rate of precipitation by 33%.